Does secure land tenure save forests? A meta-analysis of the relationship between land tenure and tropical deforestation - Robinson, B.E.; Holland, MB; Naughton-Treves, L. (Elsevier, 2014)
Deforestation and degradation are tied to a complex array of socioeconomic and political factors. Many assume that among the most important of these are the particular bundles of rights regulating who can benefit from land (tenure form) and the overall assurance that those rights will be upheld (tenure security). This paper reviews literature that connects forest outcomes and land tenure to better understand broad interactions between tenure form, security and forest change. Papers from economic theory suggest tenure is embedded in a broader socioeconomic context, with the potential for either a positive or negative conservation impact on forested land. Empirically, we find 36 publications that link land cover change to tenure conditions while also controlling for other plausibly confounding variables. Publications often investigate more than one site and more than one form of tenure, so from these we derive 118 cases linking forest change with a specific tenure form in a particular location. From these cases, we find evidence that protected areas are associated with positive forest outcomes and that land tenure security is associated with less deforestation, regardless of the form of tenure. We conclude with a call for more robust identification of this relationship in future research, as well as set of recommendations for policymakers, particularly as forest carbon incentive programs such as REDD integrate further into national policies.